Creating a Positive Workplace for Your Associates - Amanda M. Ruth; Chip Crawford; Allen F. Wysocki; Karl W. Kepner (EDIS)
This is EDIS document HR 012, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published May 2002.